Isoprenoid Glycerol Dialkyl Glycerol Tetraethers (isoGDGTs) from Lake Fazilman, Uzbekistan - Dugerdil, Lucas; Ménot, Guillemette; Peyron, Odile; Egamberdieva, Dilfuza; Jouffroy-Bapicot, Isabelle; Vannière, Boris; Alimov, Jakhongir; Luneau, Elise; Lhuillier, Johanna; Joannin, Sébastien (In: Dugerdil, L et al. (2025): Holocene multi-proxy analyses from Lake Fazilman, Uzbekistan: pollen, NPPs, GDGTs, XRF, magnetic susceptibility, climate and vegetation quantitative reconstructions [dataset bundled publication]. PANGAEA, https://doi.pangaea.de/10.1594/PANGAEA.987394 (DOI registration in progress), 2025)
This data table contains the concentration of the major isoprenoid Glycerol Dialkyl Glycerol Tetraethers (isoGDGTs) of a 227 cm-long core core from Lake Fazilman (Fazilman kul, 40.550406 N, 66.589361 E; 1637 m a.s.l.), collected in July 2021 with a 50 cm Russian corer. Mainly, each sample of one cm³ of sediment, after a 24 hours lyophilization and weighing, was crushed. The total lipid content (TLC) was twice extracted from the sediment with a DCM:MeOH (3:1) solvent extraction catalysed by microwave at 70 °C and under pressure. Then, to separate GDGTs from other lipids, the TLC was filtered on SPE cartridges and concentrated in vials. External C46 GDGTs were added as internal standard in order to estimate the Fazilman GDGTs absolute concentration (Huguet et al., 2006). GDGTs were injected in hexane:iso-propanol (99.8:0.2) solvent for a high performance liquid chromatography mass spectrometry (HPLC-APCI-MS, Agilent 1200) analysis in LGLTPE-ENS de Lyon laboratory. Then each compound was manually integrated using the m/z ratio and relative abundances in order to identify isoGDGTs (Liu et al., 2012). The external standard (C46) and the concentration of the different isoGDGTs is given in nanogrammes per one gramme of sediment. The sample depth is given in centimeters and the age in year calibrated BP (age-depth model performed with BACON and the IntCal20 calibration curve based on 15 radiocarbon dating; Blaauw et al., 2011; Reimer et al., 2020).
Keywords: Arid Central Asia; biomization scheme; climate reconstruction; GDGTs; Holocene; human impact; Magnetic susceptibility; plant functional traits; Pollen; Uzbekistan; XRF